Root Extract of a Micropropagated Prunus africana Medicinal Plant Induced Apoptosis in Human Prostate Cancer Cells (PC-3) via Caspase-3 Activation. (25th January 2022) - Komakech, Richard; Yim, Nam-Hui; Shim, Ki-Shuk; Jung, Haiyoung; Byun, Jae-Eun; Lee, Jun; Okello, Denis; Matsabisa, Motlalepula Gilbert; Erhabor, Joseph O.; Oyenihi, Omolola; Omujal, Francis; Agwaya, Moses; et al.
Abstract : Prostate cancer is one of the major causes of cancer-related deaths among men globally. Medicinal plants have been explored as alternative treatment options. Herein, we assessed the in vitro cytotoxic effects of 70% ethanolic root extracts of six-month-old micropropagated Prunus africana (PIR) on PC-3 prostate cancer cells as an alternative to the traditionally used P. africana stem-bark extract (PWS) treatment. In vitro assays on PC-3 cells included annexin-V and propidium iodide staining, DAPI staining, and caspase-3 activity analysis through western blotting. PC-3 cells were exposed to PWS and PIR at different concentrations, and dose-dependent antiprostate cancer effects were observed. PC-3 cell viability was determined using CCK-8 assay, which yielded IC50 values of 52.30 and 82.40  μ g/mL for PWS and PIR, respectively. Annexin-V and PI staining showed dose-dependent apoptosis of PC-3 cells. Significant (p < 0.001 ) percent of DAPI-stained apoptotic PC-3 cells were observed in PWS, PIR, and doxorubicin treatment compared with the negative control. PWS treatment substantially elevated cleaved caspase-3 levels in PC-3 cells compared with the PIR treatment. These results provide evidence for the antiprostate cancer potential of PIR and sets a basis for further research to enhance future utilization of roots of young micropropagated P. africana for prostate cancer treatment as an alternative to stem bark. Moreover, micropropagation approach may help provide the required raw materials and hence reduce the demand for P. africana from endangered wild population.